Spatial Epidemiology of Cancer: data types, spatial aggregation and geographical patterns in mainland Portugal - Roquette, Rita (2019)
Tese de doutoramento em Information Management - Specialization in Geographical Information Systems, apresentada à NOVA Information Management School of Universidade Nova de Lisboa, 2018